Polimorfismos genéticos dos receptores de estrogênio α e β estão associados a medidas craniofaciais em pacientes com deformidade dentofacial - Lago, Camila (2020)
Dentofacial deformities are characterized by changes in craniofacial development that affect the skeleton and dental part of the individual, often causing functional and aesthetic impairment. Craniofacial development is influenced by several factors, whether genetic or environmental. The literature has associated genetic polymorphisms with facial growth, including polymorphisms of the Estrogen Receptor 1 (ESR1) and Estrogen Receptor 2 (ESR2) genes. The objective of this work was to evaluate possible associations between polymorphisms of the ESR1 (rs2234693 and rs9340799) and ESR2 (rs1256049 and rs4986938) genes and cephalometric measurements in individuals with dentofacial deformities. Individuals in preoperative preparation for orthognathic surgery were selected at Federal University of Paraná and Positivo University. The cephalometric measurements of all patients were obtained by means of cephalometric tracings performed from the profile teleradiography in the Dolphin 2D software. For genetic analysis, patients' DNA was extracted from oral mucosa epithelial cells and was genotyped using the real-time PCR technique (Applied Biosystems 7500 Real-Time PCR System), using TaqMan ™ technology (Applied Biosystems). The data found were submitted to statistical analysis, through the Kolmogorv-Smirnov, MannWhitney and Kruskall-Wallis tests, using the IBM SPSS software version 24.0. It was considered a significance level of 0.05. The rs1256049 polymorphism showed an association with the cephalometric measurements Posterior Facial Height (S-GO) (p = 0.038) and Anterior Facial Height (N-Me) (p = 0.039). And the rs9340799 polymorphism showed an association with the Upper Gonial Angle (Ar-Go-N) cephalometric measure (p = 0.024). The other measures were not associated with the studied polymorphisms.